Analisis Perilaku Harga Pokok Mahasiswa dan Perilaku Biaya - Fikri, M. Ali; Rakhmawati, Intan; Atikah, Siti; Muhsyaf, Saipul Arni (Empiricism Journal, 2026)
Penelitian ini bertujuan untuk menganalisis harga perolehan mahasiswa dan alokasi biaya yang dibelanjakan mahasiswa semenjak mereka dilahirkan sampai dengan usia perkuliahan mereka, yaitu kegiatan dipandang melalui perspektif akuntansi. Penelitian ini berusaha melihat perilaku biaya mahasiswa berdasarkan biaya sekolah (sekolah, listrik, air, telfon, makan, minum, kost, dll), biaya entertain (meliputi biaya menonton, bermain, dll), dan biaya lainnya (biaya tak terduga, kendaraan, sakit, dll). Responden dalam penelitian menggunakan sebanyak 100 orang mahasiswa dengan rata rata usia 20 s/d 21 tahun yang telah menempuh pendidikan akutansi semester V ke atas. Responden diminta untuk menghitung biaya yang dikeluarkan sejak kecil sampai menempuh perkuliahan. Berdasarkan menggunakan ststistik Anova diperoleh hasil terdapat perbedaan antara ketiga jenis biaya tersebut, dan biaya yang paling besar dikeluarkan yaitu biaya lain-lain, dilanjutkan dengan biaya sekolah dan terakhir biaya entertain. Adapun jumlah rata rata biaya yang dikeluarkan oleh mahasiswa sejak kecil hingga dewasa sebesar Rp.756.850.605 per orang. Analysis of Student Cost Behavior and Cost Behavior Abstract This study aims to analyze students’ acquisition cost and the allocation of costs incurred from birth until they reach college age, viewed from an accounting perspective. Specifically, this study examines student cost behavior based on three categories: school-related costs, including tuition, electricity, water, telephone, food, beverages, boarding or lodging costs, and other related expenses; entertainment costs, including expenses for watching movies, recreation, leisure activities, and similar activities; and other costs, including unexpected expenses, vehicle acquisition, medical expenses, and other incidental costs. The respondents in this study consisted of 100 students, with an average age of 20 to 21 years, who had completed accounting courses from at least the fifth semester level. The respondents were asked to calculate the costs incurred from childhood until they entered higher education. Using ANOVA statistical analysis, the results show that there are differences among the three categories of costs. The largest cost category is other costs, followed by school-related costs, while entertainment costs represent the smallest proportion. The average total cost incurred by each student from childhood to adulthood is Rp756,850,605.